The Angst of the Everyday:: Using Narrative to Provoke an Affective Understanding of Adolescence - Bell, Katherine (Narrative Matters)

(untitled) (The University of New Brunswick, 2011)
This paper is written as a reflection on an interdisciplinary course I have recently taught on adolescence. I begin by noting the difficulties of negotiating theoretical claims and disciplinary insights about adolescence with a more embodied understanding of how it feels to be an adolescent, which, I argue, helps to humanize and enrich discussions and debates over the parameters of adolescent experience. I describe two narratives that served as springboards for deeper affective considerations of adolescent experience in my course: Paul Feig's Freaks and Geeks (1999) and Alice Munro's series of short stories, The Lives of Girls and Women (1971). I conclude with a brief commentary on narrative ethics, which helps me contemplate the ways in which imaginative narrative is a strong addition to an interdisciplinary study course.